The diet of a declining Red-billed Chough Pyrrhocorax pyrrhocorax population on Islay, Scotland. Issue 3 (3rd July 2018) - MacGillivray, Fiona S.; Gilbert, Gillian; McKay, Clive R.
ABSTRACT: Capsule: We quantify Red-billed Chough Pyrrhocorax pyrrhocorax diet from faecal samples collected on Islay. Dung invertebrates formed the majority of prey biomass in dune pasture and Tipulid larvae in mixed pasture but Aphodius larvae were scarce in the diet, whereas they had been a major component in the 1980s. There are management implications from the indication of a reduction in availability of preferred food.